Significance of neutrophil lymphocyte ratio and platelet lymphocyte ratio in lung cancer - Ashumi Gupta; Urvashi Singh; Mohan Lal Gupta; Narendra Mogra; Medha Mathur (Tropical Journal of Pathology and Microbiology, 2019)
Background: An underlying inflammatory state is an important contributor to carcinogenesis and progression of tumors. Many of the etiological factors in development of lung cancer are linked to persistent inflammation. Neutrophil lymphocyte ratio (NLR) and Platelet lymphocyte ratio (PLR) are markers of systemic inflammatory response that have shown clinical significance in cancer, according to recent research.Objective: To evaluate NLR and PLR in lung cancer and compare these parameters in healthy controls.Materials and Methods: Clinicopathological details and hematological parameters of complete blood counts were recorded for 106 patients of lung cancer and 106 healthy controls retrospectively. NLR and PLR values were evaluated and compared in the two groups.Results: NLR and PLR were significantly elevated in lung cancer patients (NLR 4.44±2.98; PLR 162.72±96.15) as compared to control group (NLR 1.90±0.67, PLR 115.15±29.15) with p value <0.05. NLR showed a sensitivity of 74.5% and specificity 85.8% at optimal cut off value (2.5), as per Receiver operating characteristics (ROC) curve analysis. ROC curve analysis for PLR showed sensitivity 48.1% and specificity 87.8% at optimal cut off value (148.7).Conclusion: NLR and PLR are significantly raised in lung cancer. This reflects an underlying inflammatory state that may contribute to development and progression of neoplastic disease in lung. NLR a more sensitive than PLR and may provide useful diagnostic and prognostic information in a country like India that bears a high load of lung cancer cases.